Empowering Subject Teachers’ Professionalism Through Knowledge on Guidance and Counseling - Sutirna; Suprananto; Ika Rizqi Meilya; Evi Karlina Ambarwati (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Problems faced by students during the teaching-learning process are usually directed to the Guidance and Counseling Teachers. However, problems related to the students’ understanding of subject matters are ideally handled by the subject’s teachers. Therefore, subject teachers require knowledge and skill to guide and counsel students. The purpose of this community service program was to empower the role of subject teachers in counseling students’ learning problems. The activity was carried out in the of Focus Group Discussion (FGD) involving 48 junior high school teachers in Telukjambe District, Karawang Regency. The topics covered during FGD were theoretical concepts of Guidance and Counseling and practical implementation of counseling principles. The result of these activities is an increasing understanding among the subject teachers regarding the importance of skills in counseling. This program suggests the need of continuous professional development for subject teachers to increase their skill in counseling students.